Cheaters on an aptitude test in an earlier selection hurdle are not more likely than non-cheaters to fake on a personality test in a subsequent selection hurdle. (15th April 2020) - Liu, Ying; Liu, Jiayi; Zhao, Guoxiang; Fan, Jinyan
Abstract: Within selection settings, job applicants are motivated to engage in dishonest behaviors such as cheating and faking, in order to increase their chance of getting the job. The present research investigates whether applicants engage in dishonest behaviors across selection hurdles. We place two opposite conceptual views on trial: (a) the behavioral consistency view predicting that applicants should display consistent behavior patterns (honest or dishonest) across selection hurdles, and (b) the situational specificity view positing that dishonest behaviors do not necessarily generalize across selection hurdles. Participants were 984 applicants for graduate programs at a large university in China, who went through a national entrance examination (1st hurdle) and then took an online personality test during the campus interview (2nd hurdle). The results show that (a) applicants who had cheated on the exam at the 1st hurdle were as likely to fake on the personality test at the 2nd hurdle as non-cheaters, and (b) cheaters and non-cheaters responded similarly to a warning message (over a control message) delivered at the beginning of the personality test. These findings, overall, do not support the behavior consistency view, but are more aligned with the situational specificity view.